Laparoscopic totally extra-peritoneal hernia repair for bilateral Spigelian hernias and coincident inguinal hernia: A case report. (2016) - Matsui, Shimpei; Nitori, Nobuhiro; Kato, Ayu; Ikeda, Yoshifumi; Kiatagwa, Yuko; Hasegawa, Hirotoshi; Okabayashi, Koji; Tsuruta, Masashi; Kitajima, Masaki
Highlights: Laparoscopic exploration is important to precise diagnosis of ventral hernia. Laparoscopic totally extra-peritoneal repair is feasible for Spigelian hernia. Laparoscopic exploration is also important after repairing ventral hernia. Abdominal CT in the abdominal position is useful to precise diagnosis of hernia. Abstract: Introduction: Spigelian hernia (SH) is a rare ventral hernia occurring near the lateral border of the rectus muscle. The treatment remains controversial and depends on institutional expertise. Although laparoscopic surgery is a good adaptation for the repair of ventral hernias, only a few cases have been reported in the literature. Here, we report a case of totally extra-peritoneal (TEP) repair for bilateral SHs. Presentation of case: A 74-year-old Japanese man presented with asymptomatic bulges in the right lower abdominal quadrant. On physical examination, the bulges were located to the right of the lateral border of the abdominal rectus muscle and the right inguinal region in an upright position. We diagnosed right SH and coincident homonymous ipsilateral inguinal hernia (IH) by abdominal computed tomography and planned a curative operation by laparoscopy. By first laparoscopic exploration, we found an asymptomatic SH to the left of the lateral border of the abdominal rectus muscle and performed TEP repair for all hernias. The second laparoscopic exploration after fixing the mesh in place revealed that the orifice of the right SH was scarred and stiffened by repeated prolapse. We finally eliminated the sac by ligation because of a fear causing of reduction en masse of the SH. Discussion and conclusion: The use of laparoscopy simplified the diagnosis and facilitates the subsequent repair of the hernia. TEP approach is the ideal treatment for the simultaneous laparoscopic repair of SH and IH.